GENERAL APPROACH TO PROJECT MATERIAL RESOURCES MANAGEMENT - Svitlana Danshyna (Сучасний стан наукових досліджень та технологій в промисловості, 2021)
The subject matter of the article is the processes of managing the material resources of the project. The goal of the work is to form a generalized approach to the management of material resources project by determining and formalizing the management processes of them. The following tasks were solved in the article: the processes of managing material resources project, which based on the process approach, are formed; place of these processes in the PMBOK structure is defined, these processes are integrated with other project management processes; a formalized presentation of the project management processes of the project is given; tools and methods of managing material resources of the project are identified. The following methods used are – methods of system analysis, decision-making theory, and inventory management theory. The following results were obtained – with target to make informed management decisions, it was proposed to allocate a separate area of knowledge, within which the processes of the management of material resources of the project are formed, their possible connection with the groups of PMBOK processes is shown. Based on the process approach, presentations of the processes were formalized. They are elements of managing material resources of projects. They define inputs and outputs, show interrelations with other processes of a specific area of knowledge, provide basic recommended tools and methods. Conclusions: the processes management resource described in the PMBOK methodology are analyzed. This made it possible to form possible directions for improving the project's resource support. It is noted that the solution to this problem depends on the management of the material resources of the project. A separate area of knowledge has been highlighted, within the framework of the processes of management of material resources project – the processes of evaluating material resources, procurement management and supply, distribution of material resources, managing material resources. They define inputs and outputs, show interrelations with other processes of a specific area of knowledge, provide basic recommended tools and methods. The results obtained can be useful when managing projects at any stage of the life cycle.